The sociology of Law as a sub-discipline of Sociology - Guibentif, P. (Portuguese Journal Of Social Sciences, 2003)
The division of sociology into different sub-disciplines plays an important role in the discipline's development, and the establishment of a particular sub-discipline has strategic and cognitive implications for those engaged in the research of the particular topic in question, as well as for sociology in general. This is why the choice of actively contributing to such a field deserves to be thoroughly discussed. The present paper tackles the case of sociology of law, a sub-discipline whose position between jurisprudence and social sciences has always been rather uncomfortable, but whose relevance is hardly questionable at a time of rapid change in the contents, modes of dissemination and implementation of social norms.